(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This work aims to make a critical analysis of the police fiction work entitled “The case of clandestine land subdivision” written by José Clemente Pozenato, in light of the 1988 Federal Constitution and the Brazilian legal system that governs the subdivision of urban land, understand the fundamental right to housing versus the clandestinity of popular occupations in Brazil. For this purpose, the hypothetical-deductive methodology was used from a literature review in a qualitative analysis, through the problem generated by the paradox of clandestine subdivision in the face of the collision of two fundamental principles, notably, the right to housing and the social function of cities.